STRATEGI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DPPPA) KABUPATEN KARAWANG DALAM PROGRAM PERAN SERTA DAN KESETARAAN GENDER DALAM PEMBANGUNAN - Lestari, Rizky Dwi; Hakim, Lukmanul (Jurnal Politikom Indonesiana, 2019)
The results of this study indicated that the Strategy carried out by the Women's Empowerment and Child Protection Office of Karawang Regency, as a goal to accelerate the role of women and gender equality in various fields of development. At the Goal, the objective increased the role of women in politics. It improved gender equality in development planning documents. The implementation environment of the strategy and the threatening external environment came from the influence of the Patriarchal culture. Theunpreparedness of women in various fields of development and incomplete understanding of gender. Theopportunity got great support from the Karawang Regent. The internal environment was supported by good organizational capacity. Determining Direction carried out with each SKPD in Karawang who has a gender analysis workflow method namely (Gender Analysis Pathway) GAP and (Gender Budget Statment) GBS by targeting a minimum of 10 SKPD and maximizing the quota of 30% women to be legislated until the target of Karawang DPRD Chair is female. The action was carried out by providing socialization to the SKPD to include the work method of gender analysis in each development planning document and providing training needed by female legislative candidates. Learning was carried out by conducting direct socialization to the Head of the SKPD who has the power in the process of making planning documents and pressing political parties to increase the presence of female party cadres in each training made.